Simulation of Tangential Excision. Issue 5 (September 2015) - Gallagher, James J.; Goldin, Ian M.; O'Sullivan, Geoffrey M.; Silverman, Elliott L.; Mitchell, Katrina B.; Yurt, Roger W.
<x xml:space="preserve">Abstract</x> A foundational skill in burn surgery is tangential excision (TE). The purpose of this study was to develop a simulation model for TE, hypothesizing that simulation could be used in surgical training. TE simulation was created using the TE knife, foam, mineral oil, and base. Subjects, surgeons, or surgeons in training, were given a pre- and post-task questionnaire about experience with TE. Subjects were divided into three TE experience groups: novice—none, intermediate—some, and expert—TE in current or past practice. The task was to excise pre-marked rectangles, generating four excisional products (EPs). Evaluators blindly assessed performance by EP analysis using a novel scoring tool and reviewed videos using a modified objective structured assessment of technical skill (OSATS) rubric. Inter-rater reliabilities and P values were obtained, comparing Novice and Intermediate with Expert scores. Forty subjects completed the study: 16 were identified as TE novices, 17 as intermediates, and seven as experts. All EPs and videos were reviewed blindly by two evaluators using the EP scoring tool and OSATS methodology, respectively. Intraclass correlation coefficients were calculated to measure inter-rater reliabilities, which were acceptable (ICC => 0.42) for OSATS, time, and EP analysis: border and texture. Statistical differences between Novice and Expert scores were found (P < .0100, P < .0200, P < .0025, and P < .0005, respectively). Statistical differences between Intermediate and Expert scores were also found (P < .0100, P < .0200, P < .0100, and P < .0025, respectively). Post-simulation survey results showed experts 86% of the time agreeing or strongly agreeing that the simulation was similar to the clinical skin and 100% felt it would be a useful for training before clinical performance. Simulation for TE was successfully created to blindly discern level of TE experience. Participants agreed that simulation could play an essential role in burn surgical training.